Wealth opportunities in commercial real estate : management, financing and marketing of investment properties - Grabel, Gary (Hoboken, New Jersey : John Wiley & Sons, 2012)
"Commercial real estate investing is a strong investment choice for those with the right perspective and the patience to see their investment through. It is essential to know the basics of the real estate game including how to evaluate a real estate transaction and how to create value before you buy real estate at any level. Author Gary Grabel understands that to succeed in real estate, one must take the time to learn the basics and build on the skill set to properly evaluate investment opportunities and create value. The book covers a broad range of topics from basic terminology and analysis to leasing, financing, marketing, management, structuring a partnership, real estate tax consequences, buying and selling property, and the steps needed to preserve wealth. The book sets forth a practical step-by-step process on how to acquire real estate through a real estate vehicle to build significant wealth over time"-- Provided by publisher
1. An overview of the problem, a solution, and a game plan -- 2. The basics -- 3. Detailed financial analysis -- 4. Lease analysis -- 5. Real estate financing -- 6. Real estate taxation -- 7. Acquisitions and dispositions -- 8. Case studies -- 9. Dwvwlopment of rehabilitation ( build to a 12 percent yield) -- 10. Marketing, leasing, and management -- 11. Partnership structuring and deal restructuring -- 12. Keeping the money
Includes index
Keywords: Commercial real estate; Real estate investment